La mimesis dell’esperienza quotidiana. L’influenza del pensiero di John Dewey nella socially engaged art statunitense (Itinera, 2024)
The text aims to analyze the concept of “mimesis” as an artistic practice of transformation of the ordinary within the so-called “socially engaged” and “community-based art practices” in the United States since the 1990s. As a theoretical reference, the text explores the concept of experience expressed by the American philosopher John Dewey in his Art as Experience (1934), subsequently taken up by various curators and artists such as Mary Jane Jacob, Mark Dion and Pablo Helguera.Since the 1990s, within the world of contemporary art a social and participatory trend has developed founding its place of action in the urban space and with marginalized communities as active participants. Given the collaborative attitudes, these actions soon took the name of practices moving away, even in a theoretical way, from public art and from any other type of authorial intervention in the public space. In the 2000s the critical discourse moved to the field of the value of social action (Kester, Bishop), or how to judge or not the artistry of a process that does not produce authorial works, has no spectators and takes place outside the artistic system proper. This is because these practices are based on an interdisciplinary theory which, moving from pedagogical and activist foundations, found in the thought of John Dewey its first moment of conjunction with artistic theory to the point of being recognized as a direct source for several artists and curators who worked between the 90s and 2000s. The geographical centre of this discourse is the United States as the role played by progressive education formalized in the early 1900s laid the foundations for an educational model that has also permeated artistic practice.
Keywords: experience, community, Dewey, socially engaged art, public art.